Implications of Jhonson's Behavioral Theory: Effect of Bedside Handover Sbar on 6 Patient Safety Goals - Dwi Siwi Murni Hastuti; Blacius Dedi; Witri Hastuti (Universitas Malahayati Lampung, 2026)
ABSTRACT This research was carried out because patient safety incident problems that occurred in the span of 2025, which reflected that patient safety goals have not been optimally achieved. In addition, there is a problem with the head nurse in ensuring that the handover process runs according to standards. This study aims to analyse the influence of SABR bedside handover on 6 aspects of patient safety goals. This study is included in the category of quantitative research with a quasi-experimental design of two grouppretest-posttest design, which involves an experimental group of 47 respondents, namely inpatient nurses who received SPAR-based bedside hand over training based on Johnson behaviour, and a control group of 47 nurses who only received leaflet bedside hand over based on SBAR is based on Johnson’s behaviour. The results of the analysis concluded that bedside handover SBAR has a positive and significant effect on the aspect of patient safety goals. SBAR bedside handover has been proven to improve nurses' ability to achieve 6 patient safety goals. Keywords: Bedside Handover, SBAR, Patient Safety Target.